O Anti-Counterfeiting Trade Agreement e a derrota de uma alternativa para o sistema internacional do enforcement dos direitos de propriedade intelectual - Fazano Filho, Jose Humberto (2020)
The main objective of this dissertation is to reveal the reasons for the defeat of the Anti-Counterfeiting Trade Agreement, which is a plurilateral international treaty that arose with the declared promise of addressing the problem of piracy and counterfeiting in the digital age by updating and harmonizing the system of international enforcement of intellectual property rights. To this end, the research is divided into three stages, each corresponding to a chapter. The first part is intended to reveal the international system of enforcement of intellectual property rights that ACTA aimed to update and harmonize. In the second stage, the problem of piracy and counterfeiting in the digital age will be addressed, as these are the arguments that justify ACTA. It will demonstrate the relationship between the different positions seen in the polarized and ideologized debate represented by the Development and Expansion Agendas, and the importance of this distance for the genesis of ACTA. In the third stage, the formation of an interest group will be studied in order to negotiate a new agreement through the plurilateral negotiation technique. The reasons for the defeat of ACTA will be demonstrated through the analysis of its evolution and the response of public opinion that was organized through the Internet and the means made possible there. The aim is to demonstrate that several factors contributed to the defeat of ACTA, which, despite this, was born under a legitimate justification and aimed at attacking a problem characteristic of the new digital era